Social work science - Shaw, Ian 1945- (Columbia University Press, 2016)
Ian Shaw threads together advances in modern technology, practice skills and evidence-based practice, the history of scientific claims in social work practice, and the methods of social work research to demonstrate the significant role science can play in the management of human emotions and behavior. Shaw links scientific and social work knowledge through the core themes of quality evidence, critical learning and understanding, and the skilled evaluation of the subject